Predicting longitudinal trajectory of bone mineral density in paediatric systemic lupus erythematosus patients. Issue 10 (22nd March 2012) - Lim, Lily Siok Hoon; Benseler, Susanne M; Tyrrell, Pascal N; Harvey, Elizabeth; Herbert, Diane; Charron, Martin; Silverman, Earl D
Abstract : Objectives: (1) To identify the average lumbar spine (LS) bone mineral density (BMD) trajectory in paediatric systemic lupus erythematosus (pSLE) patients, and (2) to identify predictors of BMD trajectory. Methods: 68 consecutive newly diagnosed pSLE patients prospectively followed in our lupus cohort with three annual dual energy x-ray absorptiometry (DEXA) examinations were studied. Low LS BMD was defined as z-score ≤−2.0. Baseline and longitudinal clinical features including disease activity, treatment and bone physiology markers were collected. Hierarchical linear modelling was used to model trajectory of LS BMD and identify predictors. Results: Women constituted 84% of the cohort and median age at diagnosis was 13.1 years. The mean LS BMD z-scores decreased over time ( − 0.42 at first, −1.02 at second and −1.11 at third DEXA). Initially 9% of patients had a low BMD, which increased to 19% by 3 years after diagnosis. 35% of patients deteriorated in BMD category from the first to third DEXA. LS BMD (adjusted by height-for-age z-score) followed a general deteriorating trajectory of −0.06 z-score/year from diagnosis. Increased rate of deterioration of BMD trajectory was predicted by pubertal status at diagnosis, increased interval cumulative steroid exposure and decreased weight z-scores. Conclusions: The LS BMD of pSLE patients followed a general deteriorating trend over time and could be predicted by a combination of pubertal status at diagnosis, interval cumulative doses of steroids and weight z-scores. Interval cumulative steroid dose represents an important target that clinicians may modify to ameliorate deteriorating BMD trajectory over time.